Mineral contents of selected marine fish and shellfish from the west coast of Peninsular Malaysia - Abd Aziz @ Mughni, Nurnadia; Azlan, Azrina; Ismail, Amin; Abd. Shukor, Mohd. Yunus; Halmi, Mohd Izuan Effendi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The study was conducted to determine the mineral contents of 20 species of marine fish and 4 species of shellfish from the west coast of Peninsular Malaysia.Overall, the contents of micro minerals in all samples were below the permissible limits; except for oyster; with copper slightly higher than the limit set by FAO/WHO (1984), but below the limit set by Malaysian Food Regulations (1985); and zinc content higher than the limit set by Malaysian Food Regulations (1985), but below the limit set by FAO/WHO (1984). Meanwhile for macro minerals, most samples contained comparable sodium contents, significantly lower of potassium contents, higher calcium contents, and extremely higher of magnesium contents compared to the common ranges reported in the literatures. All samples were good sources of micro and macro minerals and could provide multi-health benefits if consumed in recommended amounts.